Utilisation of Funds Under Article 275 (1) A Review - Planning Commission (Planning Commission, 1997)
The document is a review by the Programme Evaluation Organisation within the Government of India's Planning Commission, assessing how funds allocated under Article 275(1) are utilized. This article allows for grants to be made to states for the development of Scheduled Tribes (STs) and associated administrative areas, aimed at improving their welfare. The review highlights objectives, methodology, data collection, and evaluations surrounding these funds from 1992 to 1996. The review finds that while central allocations have increased significantly over the years, the practical utilization of these funds has often fallen short of targeting the intended beneficiaries. A stronger focus on genuine welfare projects for tribal communities, as outlined in the guidelines, is needed for the funds to make a meaningful impact.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission
Keywords: Utilisation of Funds; Programme Evaluation Organisation; Article 275(1); Utilization Patterns; Ambiguity in Guidelines; Ineffective Planning; Weak Coordination; Aligned planning; Transparency